Moving hearts: How mnemonic labour (trans)forms mnemonic capital. (February 2021) - Reading, Anna
This study explores how memory forms may be understood through an economic lens tracing how the labour of remembering adds value to and (trans)forms memories. The study focuses on embodied memories and imaginaries of migration and belonging and the ways in which these are (trans)formed through mobile and social media witnessing into a collective living archive and into objectified memory forms that include art works and digital artefacts situated within global mnemonic commodity chains. Empirically, the article draws on an arts-based collaborative research project, 'Moving Hearts' carried out with the UK Migration Museum in 2016–2018 that examined embodied, artistic, and institutional memories and imaginaries of migration. Theoretically, the article builds on the growing body of research in memory studies on the economies of memory, bringing together a political economy approach to memory and work within participatory arts to provide insights into how memory forms may be understood through mnemonic labour and mnemonic capital. Specifically, it shows how the mnemonic labour of participants making, carrying and walking with clay hearts transforms memories of migration and belonging into new kinds of mnemonic capital.